Kelantan flood victims grateful to government for assistance - New Sarawak, Tribune (New Sarawak Tribune, 2013)
KOTA BAHARU: "My family and I are thankful to be able to move out in time to this flood relief centre," said Shamsiah Saufi, 41, a resident of Kampung Tasik, here, whose home was submerged by the floods last month.